2022
DOI: 10.1186/s12889-022-12538-w
|View full text |Cite
|
Sign up to set email alerts
|

Links between obesity, weight stigma and learning in adolescence: a qualitative study

Abstract: Background Educational attainment is a key social determinant of health. Health and education are linked by multiple pathways, many of which are not well understood. One such pathway is the association between being above a healthy weight and lower academic achievement. While various explanations have been put forward to explain this relationship, evidence for causal pathways is sparse and unclear. This study addresses that evidence gap. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Some scholars have proposed psychological factors, particularly related to body image stereotypes, as a potential explanation for this association. Stereotypes portraying overweight and obese individuals as lazy, lacking discipline, or less intelligent (Brownell et al, 2005;Griffiths et al, 2010;Komarraju & Dial, 2014;Krukowski et al, 2009;Langford et al, 2022;Puhl & Heuer, 2010) may adversely impact self-esteem and goal-setting, potentially leading to academic underachievement or school dropout. Li et al (2008) suggested that adiposity might affect cognitive functions, including learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have proposed psychological factors, particularly related to body image stereotypes, as a potential explanation for this association. Stereotypes portraying overweight and obese individuals as lazy, lacking discipline, or less intelligent (Brownell et al, 2005;Griffiths et al, 2010;Komarraju & Dial, 2014;Krukowski et al, 2009;Langford et al, 2022;Puhl & Heuer, 2010) may adversely impact self-esteem and goal-setting, potentially leading to academic underachievement or school dropout. Li et al (2008) suggested that adiposity might affect cognitive functions, including learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Physical WB had the strongest association with absenteeism, with children who experienced physical bullying being approximately four times more likely to skip a particular class and five times more likely to skip school compared with children who did not experience physical WB. Prior qualitative research with young adults who had high body weight during secondary school identified the strategy of becoming “invisible,” including through absenteeism, as a method of avoiding being bullied (Langford et al, 2022). Prior research has also associated youth absenteeism with being fearful (Grinshteyn & Yang, 2017), which might further explain why children in our sample who experienced physical WB were particularly likely to have school absences.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic, neurological, pulmonary, gastroenterological, and endocrine conditions are more common in children with morbid obesity. Excess adiposity can affect a child’s immediate physical and mental health, educational achievements, quality of life, self-esteem, body image, and economic mobility [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%